A visual method to detect meat adulteration by recombinase polymerase amplification combined with lateral flow dipstick. (30th August 2021) - Lin, Liyun; Zheng, Yuzhong; Huang, Huiying; Zhuang, Fenluan; Chen, Huixia; Zha, Guangcai; Yang, Peikui; Wang, Zhonghe; Kong, Meilan; Wei, Huagui; Zou, Xianghui; Lin, Min
Highlights: A visual method based on RPA and LFD for identification of meat adulteration (beef, sheep, pork, duck, chicken) was firstly developed. The identification reaction was completed within 20 min. The identification results could be determined by the naked eye. The detection limits of the RPA-LFD assays for duck, beef, sheep, chicken, and pork were 10 1 /µL, 10 2 /µL, 10 2 /µL, 10 1 /µL and 10 1 /µL, respectively. The RPA-LFD assays could differentiate species in boiled, microwaved, pressure -cooked or fried samples. Abstract: Determining the animal source in meat and meat products is crucial to prevent meat adulteration and fraud. Conventional methods require considerable operator skills, expensive instruments and are unable to provide fast mobile on-site detection systems to detect contamination of meat products. We developed a visual method based on recombinase polymerase amplification (RPA) and a lateral flow dipstick (LFD) to identify beef ( Bos taurus ), sheep ( Ovis aries ), pork ( Sus scrofa ), duck ( Anas platyrhynchos ) and chicken ( Gallus gallus ). The reaction was completed within 20 min. The results were determined by the naked eye. The detection limits of the RPA-LFD assays for duck, beef, sheep, chicken and pork were 10 1 /µL, 10 2 /µL, 10 2 /µL, 10 1 /µL and 10 1 /µL, respectively. Furthermore, the RPA-LFD assays could differentiate species in boiled, microwaved, pressure-cooked or fried samples. These RPA-LFD assays represent a rapid, mobile detection system for determining meat product contamination.